Sentecing Model For Residivists Of Illegal Mineral And Coal Mining Crimes - Kaplele, Farida -; Rohrohmana, Basir -; Budiyanto, Budiyanto - (Faculty of Law, Universitas Pekalongan, 2024)
The goal of the current normative research is to investigate how Law Number 4 of 2009 concerning Mineral and Coal Mining (also known as the Minerba Law) applies to the sentencing of recidivist offenders for offenses involving mining minerals and coal. When it comes to dealing with criminal punishments for recidivists who commit crimes related to mining and minerals, there appears to be a complete lack of legislation. This indicates a legal gap that applies to perpetrators who meet the requirements for recidivist status. Since it is governed by Book Two, Chapter XXXI covering Rules for Repetition of Crimes Relating to Various Chapters, Articles 486 to Article 488, the present Criminal Code's position on recidivists is, in theory, not a general norm in this regard. Articles 486 through 488, however, define recidivist as a criminal aggravation for the kinds of criminal crimes included in the established provisions. The criminal punishments found in the Criminal Code correspond to the penalties found in a number of specific criminal legislation that are applied to repeat or recidivist offenders.